Building Refurbishment for Energy Performance A Global Approach - Magrini, Anna.; Magrini, Anna. (Green Energy and Technology,, 2014)
In Europe, the building sector accounts for 40% of energy consumption which has a strong influence on greenhouse gas emissions. The book deals with efficient methodologies aimed to reduce greenhouse gas emissions in the building sector. This includes analyses of the building envelopes, the heating systems, the use of solar energy, and the assessment of the environmental and energy sustainability of the proposed solutions. After a brief introduction to the physical fundamentals involved in the study, results are presented to support cost-effective technical strategies to promote actions for energy saving, in the most critical fields and with the most economic advantage.